The Role Of Green Sukuk In Achieving The Sustainable Development Goals (SDGs) In Indonesia - Agung Rofianto; Arga Kusuma Prasetya; Safaah Restuning Hayati (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study examines the strategic role of Islamic finance, specifically through Green Sukuk instruments, in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia. Amidst the global urgency of climate change and the substantial funding gap for green infrastructure, this research evaluates how Green Sukuk aligns with maqasid al-shariah to foster environmental sustainability. This research employs a qualitative descriptive approach using a systematic literature review. Data were synthesized from government reports, official documents from the Ministry of Finance, and academic journals published between 2020 and 2025 to ensure contemporary relevance. The analysis reveals that Indonesia’s Green Sukuk issuance reached USD 6 billion by 2023, positioning the nation as a global leader in Islamic green finance. However, there is a significant sectoral imbalance: 97% of the funds are allocated to climate resilience and disaster risk reduction (supporting SDGs 6 and 13), while critical sectors like renewable energy and sustainable transport (supporting SDGs 7 and 11) receive less than 1%. Furthermore, the market remains heavily reliant on sovereign issuance, with minimal participation from the private sector due to a lack of fiscal incentives and concerns over